2020
DOI: 10.1186/s12951-020-00645-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of miR-29b and germacrone based on cyclic RGD-modified nanoparticles for liver fibrosis therapy

Abstract: Hepatic stellate cells (HSCs) were activated and secreted excessive amounts of extracellular matrix (ECM) proteins during pathogenetic progress of liver fibrosis. Germacrone (GMO) and miR-29b can play an important role in inhibiting growth of HSCs and production of type I collagen. GMO and miR-29b were co-encapsulated into nanoparticles (NPs) based on poly(ethylene glycol)-block-poly(lactide-co-glycolide) (PEG-PLGA). Then, NPs were modified with cyclic RGD peptides (cRGDfK). cRGDfK is an effective ligand to bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…This nanoparticle system efficiently internalized into HSCs via αvβ3-mediated endocytosis. GMO and miR-29b inhibit the proliferation of activated HSCs and collagen 1 expression, and in vivo, this nanoparticle system ameliorated CCl 4 -induced liver fibrosis in mice [37].…”
Section: Nanotargeting Of Activated Hsc Surface Proteins and Signalingmentioning
confidence: 88%
“…This nanoparticle system efficiently internalized into HSCs via αvβ3-mediated endocytosis. GMO and miR-29b inhibit the proliferation of activated HSCs and collagen 1 expression, and in vivo, this nanoparticle system ameliorated CCl 4 -induced liver fibrosis in mice [37].…”
Section: Nanotargeting Of Activated Hsc Surface Proteins and Signalingmentioning
confidence: 88%
“…Modern research has shown that furanodienone, . Germacrone not only has protective effect on acute liver injury but also inhibits the proliferation and promotes apoptosis of liver cancer cells, breast cancer cells, lung cancer cells, and glioma cells [17,18]. Chen et al found that furanodienone, a diene-type sesquiterpene isolated from the rhizomes of Rhizoma Curcumae, exhibited a potential cytotoxic effect on temozolomide-(TMZ-) resistant GBM cells in vitro by inhibiting CSPG4 and related signalling pathways [19].…”
Section: Discussionmentioning
confidence: 99%
“…HE, Masson, and Sirius‐red staining were performed as previous reported 21 . Fresh heart tissues were fixed in 4% paraformaldehyde and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…2.5 | hematoxylin-eosin (HE), Masson, and Sirius-red staining HE, Masson, and Sirius-red staining were performed as previous reported. 21 Fresh heart tissues were fixed in 4% paraformaldehyde and embedded in paraffin. Five-micron sections were obtained, deparaffinized, and rehydrated as previously described.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%